An Online Art Project Based on the Affirmative Model of Disability in Japan. (14th October 2022) - Ikeda, Satoshi; Siddiqi, Hiroko Fukuda; Mori, Mayuko; Kawajiri, Hiromitsu; Hirasawa, Misa; Kawaguchi, Takashi; Yasuda, Kaoru
Abstract: In recent years, disability has become a site for knowledge and artistic creation. In this study, local governments, universities, art museums and non‐profit organisations collaborated from 2019 to 2022 to implement an online art project for people with disabilities during the Covid‐19 era. The project's goal was to enhance the identity of people with disabilities, promote their interest in museums and artwork as local resources and engage them in society. The project was conducted in three phases with a sequence of connections using the affirmative model of disability by Swain and French (2000) as the theoretical framework. In Phase 1, we surveyed 370 people with disabilities and their supporters living in Hiroshima Prefecture to clarify the conditions promoting or hindering their appreciation of art exhibitions and the use of digital devices. In Phase 2, we conducted an online interactive appreciation workshop at a museum for seven people with disabilities based on the Phase 1 survey results. In Phase 3, an online exhibition was held using the artwork seen in Phase 2, and words and photographs were used as methods of expression. The interactive appreciation workshop and exhibition was built to provide the participants a safe and comfortable online alternative space, which led to individual empowerment and enhanced collaboration in the disability community. This study advocates the value of coexisting and co‐prosperous inclusion rather than inclusion that necessitates people gathering in the same place.